The Influence of Lecturer Competences on Students Learning Achievement of Faculty of Literature, Islamic University of North Sumatra - Asnani Asnani; Nurismilida Nurismilida (Proceedings of AICS - Social Sciences, 2017)
The purpose of this study was to determine the influence of the four lecturer competences on student learning achievement. In Law of  the Republic of Indonesia No. 14/2005 on teachers and lecturers, lecturer competences are divided into four, namely pedagogic competence, personality competence, social competence, and professional competence. These four competences will be the independent variable (X) and students learning achievement becomes the independent variable (Y). The samples of this research were students of Faculty of Literature, Islamic University of North Sumatra Medan in odd semester 2016-2017. The questionnaire was taken from lecturer competence questionnaire, State University of Padang.  This research used quantitative research. Data analysis techniques are multiple linear regression, determination coefficient, t-test, and F-test. Before conducting multiple linear regression analysis, the required condition test: normality test, multicollinearity test, and heteroscedasticity (Ghozali, 2005) had done. The study used the analysis of variance (ANOVA). In F-test, F=1.012 Ftable=2.42, FFtable. It meant that there was no influence of competence simultaneously on students’ learning achievement. In T-test, t-test ttable, so results showed that there was no significant influence between lecturer’s competences individually.  In multi linear regression analysis, the higher lecturer’s pedagogic and social competence, the higher the students’ learning achievement, and the lower lecturer’s personality and professional competence, the lower the students’ learning achievement. The findings   is there is no influence between lecturer’s competences to students’ learning achievement each and simultaneously.